EXAMINING THE ASSOCIATION BETWEEN SELF-CONTROL AND MOBILE GAME ADDICTION - MOROESI G. PITIKOE-CHILOANE; BONGAZANA DONDOLO (Social Sciences and Education Research Review)
Smartphones are seen as the primary source of mobile gaming's popularity and mobile game addiction. This study investigates the link between lack of self-control and addiction to mobile gaming, with a specific emphasis on the role that smartphone addiction plays in mediating this connection. Data were collected from a convenience sample consisting of 276 students registered in Technical and Vocational Education and Training (TVET) programmes at one college. Of the participants, 58% were female, and 42% were male. The primary data were collected using a cross-sectional survey and analysed using structural equation modelling. The structural equation modelling and mediation analysis revealed that addiction to mobile games and smartphone use is highly linked to a lack of self-control. The results also indicated that smartphone addiction partially explains the pervasiveness of gaming addiction among TVET students. The research emphasised how critical it is for students to have the capacity to exercise self-control, particularly in light of the fact that modern conveniences such as smartphones are essentially an extension of one's own hands. The study recommends that higher education institutions provide support to students who are caught up in excessive time spent on smartphones. It also recommends introducing control measures so as to foster a sense of awareness and self-regulation among students, therefore encouraging them to make well-informed choices regarding the allocation of their screen time.